Traditional Market Revitalization as an Urban Catalyst in the City of Surakarta - Istijabatul Aliyah; Bambang Setioko; Wisnu Pradoto (Bandar Lampung University (UBL), 2014)
Current development in Surakarta downtown today indicates that traditional markets have improved themselves in both physical and non-physical aspects. Various revitalization efforts have been made by the government and traders community to improve services and comfort of traditional markets. The efforts start from the market façade revitalization, restoration and the overall development of market; up to social activities, competition between traders or large celebrations in the neighbourhood market. This research was conducted in Surakarta, which is aimed at: identifying the role of traditional market revitalization efforts in the development of a city. This study employs several methods of analysis, namely: 1) Spatial analysis for mapping the distribution of traditional markets in the city constellation, 2) Category-Based Analysis (CBA) to classify the revitalization of traditional markets that has an influence in the development of the city, and 3) Interactive Method of Analysis. The results of this study indicate that the presence of a constellation of traditional markets in Surakarta is dominated by the presence of Gede Market, not only as the oldest traditional market, but also as a center of economic and socio-cultural activities of the community. The role of traditional market revitalization in the development of a town is as an Urban Catalyst towards a MICE city in the sense that the revitalization effort, even done in a relatively short time and not yet covering the overall objects, is able to establish brand image of Surakarta as a city of culture which is friendly and ready to be MICE tourism city.